How representative of primary care are research active practices? Cross-sectional survey. - McManus, R; Ryan, R; Jones, M; Wilson, S; Hobbs, F (2008)
BACKGROUND: There has been a continued trend towards undertaking primary care-based research but the characteristics and generalizability of practices that participate in such research are not well known. OBJECTIVE: To compare research active and non-active practices in terms of practice demographics, disease prevalence and quality scores from the Quality and Outcomes Framework. DESIGN: Cross-sectional survey using publicly available data. SETTING: A total of 973 general practices from the West Midlands, UK. MAIN OUTCOME MEASURES: Practice population characteristics, research status, disease prevalence, clinical and non-clinical quality scores. RESULTS: Of 973 practices, 298 (31%) were defined as research active. Research active practices had younger populations (% over 65: 15.2% versus 16.2%, z = 3.95, P < 0.0001) compared to non-research active practices, were larger [median list size 6123 (interquartile range, IQR, 3642-9691) versus 4059 (IQR 2675-7060) z = 6.96, P < 0.0001] and more likely to be in deprived areas [median Townsend quintile 5 (IQR 3-5) versus 4 (IQR 3-5), z = 3.23, P = 0.001]. Disease prevalence was similar in both research active and non-active practices but the former attained higher median quality scores for both clinical [research active 534/550 (IQR 508-546) versus non-research active 525/550 (IQR 483-542) z = 4.00, P < 0.0001] and non-clinical [310/320 (IQR 283-319) versus 296/320 (IQR 265-314), z = 5.76, P < 0.0001] areas. CONCLUSION: General practices which participate in research are larger and located in more deprived areas than non-research active practices but disease prevalence is similar and research practices attain only modestly higher quality points. Research in research active practices is likely to be generalizable to the wider primary care community.